UNPACKING USER SATISFACTION IN MANDATORY E-GOVERNMENT: TESTING IS SUCCESS MODEL ON INDONESIA’S REGIONAL SYSTEM - Annisa, Rizqi; Nor, Wahyudin (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
The Regional Government Information System (RGIS) plays a crucial role in improving efficiency, transparency, and accountability in financial management. Research advances IS success model by validating DeLone & McLean framework in unique context of Indonesia’s compulsory e-government system. This study examines the effects of system quality, information quality, service quality, content relevance, and ease of use on user satisfaction, and the impact of user satisfaction on net benefits. It also investigates the mediating role of user satisfaction between these factors and net benefits. Data from 458 users across South Kalimantan’s provincial and regional governments analyzed using SEM-PLS. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Results indicate content relevance and ease of use significantly affect user satisfaction; system quality, information quality, and service quality do not. User satisfaction strongly influences net benefits. User satisfaction mediates the relationship between content, ease of use, and net benefits. These findings contribute theoretically by highlighting content and ease of use as key determinants in government information system success models. Practically, the study stresses prioritizing relevant content and usability in RGIS development to enhance benefits. This research improves understanding of how user satisfaction drives value creation in public sector information systems.